ANALISIS EKSPERIMENTAL CAMPURAN BAHAN BAKAR SOLAR DAN HASIL REAKSI ALKOHOLISIS BIODIESEL DARI PALM FATTY ACID DISTILLATE SEBAGAI BAHAN BAKAR MESIN DIESEL PADA TAMBAK UDANG - Ahmad Jibril; Faizin Adi Nugroho (Program Studi Kimia - Universitas Sari Mutiara Indonesia, 2021)
Currently, condition of the availability of energy sources derived from fossil fuels which is decreasing and increasing air pollution caused by emissions resulting from the combustion of fossil fuels, then it is time to diversify energy by developing new and renewable energy environmentally friendly by utilizing sources of raw materials derived from vegetable oils, one of them is biodiesel. Biodiesel is produced through an alcoholics’ reaction process between vegetable oil and methanol with the help of an acid or base catalyst. Furthermore, the biodiesel that has been produced is then mixed with diesel fuel in a certain ratio to be used as fuel in diesel engines. Based on the results of the experimental reaction of biodiesel alcoholics with a variable concentration of catalyst against the weight of feed palm fatty acid distillate, the optimum methyl ester result was obtained at 98.65% and the results of the analysis of the alcoholics reaction of biodiesel with the variable ratio of reagents between the weight of methanol to the weight of feed palm fatty acid distillate obtained the optimum methyl ester result at 98.33%.